Personal inhalation exposure to polycyclic aromatic hydrocarbons and their nitro-derivatives in rural residents in northern Thailand - Walaiporn Orakij (2018)
© 2017, Springer International Publishing AG. A personal inhalation exposure and cancer risk assessment of rural residents in Lampang, Thailand, was conducted for the first time. This highlighted important factors that may be associated with the highest areal incidence of lung cancer. Personal exposure of rural residents to polycyclic aromatic hydrocarbons (PAHs) and their nitro-derivatives (NPAHs) through inhalation of fine particulate matter (PM 2.5 ) was investigated in addition to stationary air sampling in an urban area. The personal exposure of the subjects to PM 2.5 ranged from 44.4 to 316 μg/m 3 , and the concentrations of PAHs (4.2–224 ng/m 3 ) and NPAHs (120–1449 pg/m 3 ) were higher than those at the urban site, indicating that personal exposure was affected by microenvironments through individual activities. The smoking behaviors of the rural residents barely affected their exposure to PAHs and NPAHs compared to other sources. The most important factor concerning the exposure of rural populations to PAHs was cooking activity, especially the use of charcoal open fires. The emission sources for rural residents and urban air were evaluated using diagnostic ratios, 1-nitropyrene/pyrene, and benzo[a]pyrene/benzo[ghi] perylene. Their analyses showed a significant contribution to emission from residents’ personal activities in addition to the atmospheric environment. Furthermore, the personal inhalation cancer risks for all rural subjects exceeded the USEPA guideline value, suggesting that the residents have a potentially increased cancer risk. The use of open fires showed the highest cancer risk. A reduction in exposure to air pollutants for the residents could potentially be achieved by using clean fuel such as liquid petroleum gas or electricity for daily cooking.